Bayesian network as a modelling tool for risk management in agriculture - Svend Rasmussen; Anders L. Madsen; Mogens Lund (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
The importance of risk management increases as farmers become more exposed to risk. But risk management is a difficult topic because income risk is the result of the complex interaction of multiple risk factors combined with the effect of an increasing array of possible risk management tools. In this paper we use Bayesian networks as an integrated modelling approach for representing uncertainty and analysing risk management in agriculture. It is shown how historical farm account data may be efficiently used to estimate conditional probabilities, which are the core elements in Bayesian network models. We further show how the Bayesian network model RiBay is used for stochastic simulation of farm income, and we demonstrate how RiBay can be used to simulate risk management at the farm level. It is concluded that the key strength of a Bayesian network is the transparency of assumptions, and that it has the ability to link uncertainty from different external sources to budget figures and to quantify risk at the farm level.
Keywords: C11; C63; D81; Q12; 330; Bayesian network; Risk; Conditional probabilities; Stochastic simulation; Database; Farm account